Dynamic Semantics - Dekker, Paul J.E. author. aut Link
VIII, 128 p.
Keywords: The integrated theory of dynamic interpretation set out here will be a surprise to advanced researchers in linguistics. It combines classical formal semantics and modern dynamic semantics without altering the fundamental paradigm. At the book’s core lies a pragmatically motivated notion of a dynamic conjunction of meanings, an idea that is worked out in full formal detail. This is applied to linguistic phenomena that involve anaphora, quantification and modality. The author demonstrates that in each area of application existing data can be neatly combined with new dynamic insights, but more importantly, there is a genuine further pay-off: the work generates treatments of phenomena that were not initially intended, with functional readings of pronouns and quantifiers, ‘Hob-Nob’ sentences, and insights into what we now call ‘Pierce’s Puzzle’. The outcome of a decade of work by the Amsterdam School of dynamic semantics, this volume condenses and reflects upon a vital body of research.